Echo’s on Narratives of ’Eminent Domain’ in Land Acquisition Law: A Theoretical Discourse - Devkota, Sanad (Tribhuvan University Law Journal, 2025)
What is earn through labour whether can be taken away by sovereign state under the notion of eminent domain or not is well read notion in land law or basically in property law around several democratic legal traditions. The sovereign space for taking private property for the governmental use basically under the legal tradition of eminent domain are also creatively expressed as part of statutory imagination and many country have recognized as formal attitude in law. The land law has long association with human civilization and is developed under different episodes and echoes. The state basically (the federal government) is legislatively empowered to take immovable property of private under the notion of eminent domain concept and this is been used in various occasions by state authorities. The state is traditionally given such authorities to use private land for the public purpose and basically justifying their takings. The taking by state authorities need to be fair, transparent, useful, procedural fairness, due process of law and need to be obviously well compensated. The issues of just term compensation is always contested in the land acquisition process and many leads to violent conflict and dispositions of the project. The notion of eminent domain the land acquisition law is also well empowered for the betterment of larger public with sacrifice of individual interest. This paper is analysis of theoretical construct like concept, theories, element, justification, limitation and few case law on practice of eminent domain in Nepal.